ISLAMIC LAW'S VIEW OF THE IDDAH OF WOMEN WHO ARE ENSNARED IN ADULTERY ACCORDING TO THE HANABILAH MADZHAB - Sofian Syaiful Rizal; Indah Firdausi (LPPM STAI Muhammadiyah Probolinggo, 2025)
Iddah is a waiting period that a woman is obliged to undergo after divorce or the death of her husband in Islamic law, which aims to ensure the purity of the bloodline and gives the woman time to consider her life decisions. Even though iddah is a common problem, problems arise when faced with women who commit adultery. There are differences of opinion among scholars regarding the obligation of iddah for women who commit adultery, whether they are pregnant or not, because the Qur'an and Hadith do not explicitly regulate this matter. This ambiguity gives rise to legal consequences that influence whether or not the marriage contract between the woman who committed adultery and the man who impregnated her is valid. In this context, the Hanabilah school of thought has a firm view that women who commit adultery are obliged to undergo iddah just like women who are divorced. This research uses the legal istinbat method to analyze Hanabilah's view which equates the iddah of an adulterous woman with the iddah of a woman who is divorced. This research is library research, using literature such as books, scriptures, and relevant notes to compare the views of scholars regarding the issue of iddah for women who commit adultery. The findings show that Hanabilah's opinion has a strong basis, although it differs from the views of other scholars. The conclusion of this study is that the obligation of iddah for women who commit adultery must be viewed as a form of justice and legal certainty in Islam.